Enhanced wound contraction in fresh wounds dressed with honey in wistar rats (rattus novergicus) (2004)
Background: Due to reports that honey accelerates wound healing, an investigation on its role in wound con- traction in fresh wounds inflicted on wistar rats was car- ried out. Method: Twenty adult male wistar rats had 2cm by 2cm square wound inflicted on their right dorsolateral trunk. They were divided into two groups. The experimental group had their wounds dressed with honey while the control group had normal saline dressing. Wound dress- ing was done every five days and measurements taken at each dressing. Wound morphology was also assessed. Results: Dressing with honey significantly enhanced percentage wound contraction on day 10 with value of 79.20±2.94 compared to control value of 53.50 ±4.32. p=0.0. The mean wound measurement on day 10 reduced significantly in honey group, 1.15±0.18 compared to con- trol group 2.38±0.28. p=0.002. However, there was no significant difference in fibroblast count per high power field in honey group 68.0 ±2.59 compared to control 90.2 17.40, p=0.242. Honey dressing increased mean blood vessel count per high power field, 18.8±3.77 albeit non significantly when compared to control value of 13.4±2.44, p=0.264. Also honey dressing caused increased granulation tissue for- mation in wounds dressed with honey compared to con- trol group. Conclusion: Our study suggests that honey dressing enhances wound contraction in fresh wounds which is one of the key features of wound healing.